Biology Students' Science Literacy Level on Genetic Concepts - Hartono, A.; Djulia, E.; Hasruddin, H.; Jayanti, U. N. A. D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Scientific literacy is one’s scientific knowledge to apply based on scientific problems. It is important for shaping generational readiness to face the challenges of the 21st century. Scientific literacy is necessary for learning Biology because it can support skills in identifying, explaining scientific phenomena, and generalizing scientific facts. However, the scientific literacy level of students in Indonesia is still relatively low, ranking 70th out of 79 countries with an average achievement of 396. Therefore, this study aims to precisely determine the scientific literacy ability of Biology students and its correlation with the scientific learning model that lecturers apply. The data collection technique was carried out by providing 15 multiple-choice Scientific Literacy questions in the field of Genetics issued by the Program for International Student Assessment (PISA). The research data were analyzed descriptively and qualitatively using the Miles and Huberman approach, which consisted of three processing steps: data reduction, data presentation, and data conclusion. The results showed that the level of students’ genetic scientific literacy was still relatively low, with scores of each class being observed at 32.63%, 42.97%, and 43.06%. Factors that indicate students’ low scientific literacy are the use of textual teaching materials, students’ misconceptions about the genetic material being studied, non-contextual learning, and low student reading power. Thus, improving the quality of teaching materials on integrated genetic material on scientific literacy and learning innovations that emphasize contextual learning and students’ reading power is necessary to increase scientific literacy as a form of competency needed in 21st-century learning.